A Randomized Evaluation of a Low-Cost and Highly Scripted Teaching Method to Improve Basic Early Grade Reading Skills in Papua New Guinea - Macdonald, Kevin (World Bank, Washington, DC, 2018)
Early grade literacy skills are crucial for children's future education and ultimately their contribution to human capital formation and economic development. A significant challenge in development is identifying low-cost interventions to improve early literacy skills in contexts characterized by varying teacher ability and severe budget constraints. This paper evaluates the impact of Papua New Guinea's randomized Reading Booster Programme, which was conducted in Madang and Western Highlands Province in 2013 and 2014, respectively. The program provided teachers with training on a highly structured teaching method that they could apply one hour per day within the teaching time allocated to reading. Using the randomized assignment of schools into the program, the paper shows that it had a substantial impact on the reading skills targeted by the program for third grade students, ranging from 0.6 to 0.7 standard deviation. Large effects on other reading skills were found for girls but not boys. The program's cost per student was approximately US$60.